Implementasi Komunikasi Organisasi dalam Mengelola Keluhan Masyarakat di Kantor Dinas Kependudukan dan Pencatatan Sipil Kabupaten Pulau Taliabu Provinsi Maluku Utara - Mus, Dessyara Linea; Malik, Saharuddin; Rahayu, Pramudita Budi (Departement of Communication Sciences, Faculty of Social and Political Sciences, UIM, 2024)
This research aims to determine the implementation of organizational communication in managing public complaints at the Population and Civil Registration Service, Taliabu Island Regency, North Maluku Province. And to find out the inhibiting and supporting factors in handling public complaints at the Taliabu Regency Population and Civil Registration Service, North Maluku Province. The research method used is a qualitative descriptive research method, with data collection techniques carried out in three ways, namely observation, interviews and documentation. Apart from that, data collection also uses data analysis techniques through data reduction, data presentation and verification/drawing conclusions. The informants in this research consisted of the Head of the Taliabu Island Regency Population and Civil Registration Service, five employees of the Taliabu Island Regency Population and Civil Registration Service. and the people of Taliabu Island Regency number five people.